Intratumoral treatment of smaller mouse neuroblastoma tumors with a recombinant protein consisting of IL-2 linked to the Hu14.18 antibody increases intratumoral CD8+ T and NK cells and improves survival - Yang, Richard K. (Springer Berlin Heidelberg, 2013)
Hu14.18-IL2 is an immunocytokine (IC) consisting of human IL-2 linked to hu14.18 mAb, which recognizes GD2 disialoganglioside. Phase II clinical trials of intravenous-hu14.18-IL2 (IV-IC) in neuroblastoma and melanoma are underway, and have already demonstrated activity in neuroblastoma. In our Phase II trial, lower neuroblastoma burden at the time of treatment was associated with a greater likelihood of clinical response to IV-IC. We have previously shown that intratumoral-hu14.18-IL2 (IT-IC) compared to IV-IC results in enhanced local and systemic antitumor activity in tumor-bearing mice. We utilized a mouse model to investigate the impact of tumor burden on hu14.18-IL2 treatment efficacy in IV- versus IT-treated animals. Studies presented here describe the analyses of tumor burden at the initiation of treatment and its effects on treatment efficacy, survival, and tumor-infiltrating leukocytes in A/J mice bearing subcutaneous NXS2 neuroblastoma. We show that smaller tumor burden at treatment initiation is associated with increased infiltration of NK and CD8+ T cells and increased overall survival. NXS2 tumor shrinkage shortly after completion of the 3 days of hu14.18-IL2 treatment is necessary for long-term survival. This model demonstrates that tumor size is a strong predictor of hu14.18-IL2-induced lymphocyte infiltration and treatment outcome. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s00262-013-1430-x) contains supplementary material, which is available to authorized users.